UJIAN AKHIR NASIONAL 2003-2005: ANTARA KEBIJAKAN PEMERINTAH DAN PENINGKATAN MUTU PENDIDIKAN - Yuniarasari, Lucy Rizky (2017)
This thesis was titled "Ujian Akhir Nasional 2003-2005: Between Government Policy and Education Quality Improvement ". This thesis comes from the main problem how role of the government for improving the quality of education through Ujian Akhir Nasional and impact on quality of national education. The purpose of this research (1) to Describe background of the standard establishment Indonesian national education. (2) to describe background as planned from Ujian Akhir Nasional 2003-2005 in Indonesia. (3) Describe the impact of government policy on evaluation system of Ujian Akhir Nasional 2003-2005 the quality of education. The method used by writer is based on the historical method, in which the method includes several phase such as heuristics, criticism, interpretation and historiography. Based the results from the research, the establishment background national education standards is strongly influenced by the government efforts in improving the quality of education in order to face the global demands. The extentsive of Indonesia also affects establishment of national standards to facilitate the government in condition mapping of Indonesian education. The background of Ujian Akhir Nasional is the implementation of the national standardization policy and completion of the previous education evaluation policy. Establishment of Ujian Akhir Nasional are expected to improve the quality of education in practice there was a incompatibilty between the evaluation tool with the goal of education to be achieved. The results of this research are expected to increase literature on the history of Indonesian education and can be developed for the next research. ---- Skripsi ini berjudul "Ujian Akhir Nasional 2003-2005; Antara Kebijakan Pemerintah Dan Peningkatan Mutu Pendidikan". Skripsi ini berasal dari permasalahan utama yakni bagaimana peran pemerintah dalam meningkatkan mutu pendidikan melalui Ujian Akhir Nasional serta dampaknya terhadap mutu pendidikan nasional. Tujuan penelitian ini adalah (1) Mendeskripsikan latar belakang penetapan standar pendidikan nasional Indonesia. (2) Mendeskripsikan latar belakang dirancangnya Ujian Akhir Nasional 2003-2005 di Indonesia. (3) Mendeskripsikan dampak kebijakan pemerintah tentang sistem evaluasi pendidikan Ujian Akhir Nasional 2003-2005 terhadap mutu pendidikan. Metode yang digunakan oleh peneliti berdasarkan pada metode historis, di mana metode tersebut meliputi beberapa tahapan seperti heuristik, kritik, interpretasi dan historiografi. Berdasarkan hasil penelitian, latar belakang penetapan standar pendidikan nasional sangat dipengaruhi oleh upaya pemerintah dalam peningkatan mutu pendidikan guna memenuhi tuntutan global. Luasnya wilayah Indonesia juga mempengaruhi penetapan standar nasional untuk memudahkan pemerintah dalam memetakan kondisi pendidikan Indonesia. Adapun latar belakang penetapan Ujian Akhir Nasional ini merupakan implementasi dari kebijakan standarisasi nasional serta penyempurnaan dari kebijakan evaluasi sebelumnya. Penetapan Ujian Akhir Nasional yang diharapkan dapat meningkatkan mutu pendidikan dalam praktiknya ternyata terjadi ketidak sesuaian antara alat evaluasi dengan tujuan pendidikan yang ingin dicapai. Hasil penelitian ini diharapkan dapat menambah literatur mengenai sejarah pendidikan Indonesia dan dapat dikembangkan pada penelitian selanjutnya.